2007
DOI: 10.1016/s1473-3099(06)70684-3
|View full text |Cite
|
Sign up to set email alerts
|

WHO Rapid Advice Guidelines for pharmacological management of sporadic human infection with avian influenza A (H5N1) virus

Abstract: Recent spread of avian influenza A (H5N1) virus to poultry and wild birds has increased the threat of human infections with H5N1 virus worldwide. Despite international agreement to stockpile antivirals, evidence-based guidelines for their use do not exist. WHO assembled an international multidisciplinary panel to develop rapid advice for the pharmacological management of human H5N1 virus infection in the current pandemic alert period. A transparent methodological guideline process on the basis of the Grading R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
121
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(126 citation statements)
references
References 32 publications
2
121
0
3
Order By: Relevance
“…Therefore, the European Centre for Disease Prevention and Control (ECDC) launched the development of guidance on the public health management of sporadic cases of meningococcal disease. This involved systematic literature reviews and the application of GRADE methodology [40][41][42][43] to grade the evidence and strength of recommendations [44]. In this paper, we present the results of a systematic literature search performed as part of this project to search for direct and indirect evidence on the effectiveness of chemoprophylaxis in educational settings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the European Centre for Disease Prevention and Control (ECDC) launched the development of guidance on the public health management of sporadic cases of meningococcal disease. This involved systematic literature reviews and the application of GRADE methodology [40][41][42][43] to grade the evidence and strength of recommendations [44]. In this paper, we present the results of a systematic literature search performed as part of this project to search for direct and indirect evidence on the effectiveness of chemoprophylaxis in educational settings.…”
Section: Introductionmentioning
confidence: 99%
“…Although the cumulative number of confirmed patients remains relatively small, the scientific community agrees in considering the emergence of a new highly pathogenic H5N1 influenza pandemic as a real concern [1][2][3] . So far, the only drugs approved to treat avian flu infected patients are the neuraminidase inhibitors Tamiflu (oseltamivir) and Zanamivir (relenza) 4 . These drugs target the enzyme neuraminidase that is responsible for allowing budding progeny virus to be released from the surface of infected cells by cleaving the terminal neuraminic acid residues from the glycan structures on the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this issue can only be addressed through observational studies. Despite limited empirical evidence, the World Health Organization (WHO) reported that oseltamivir improved survival (14) and recommended treatment with oseltamivir because of high mortality rates associated with infl uenza A virus (14,15). Patients from northern Vietnam are described in detail.…”
mentioning
confidence: 99%